Normalization of Religious Hegemony as Destructive Narrative and Bio-Politics in Minahasa - Frinsly Kaat, Thiosani; Lauterboom, Mariska (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
This research analyzes the normalization of religious hegemony as a bio-political text in controlling the socio-religious movements of the Minahasa community through political truth. Using a qualitative approach with an analytical-descriptive method, this study analyzes the process of religious hegemony normalization. Data collection is conducted through literature studies. Christianity, as a world religion, has become a bio-political text for religious elites to control and legitimize actions of right and wrong within society through dogma. Normalizing theological narratives as an instrument of the elite has become a sublimated ideology. The religious hegemony of ‘Christianity’ has shaped a singular episteme (knowledge) and rejected local wisdom texts in the name of Minahasa’s traditions. First, the study discusses how Christianity, specifically the Evangelical Christian Church in Minahasa (GMIM), has formed bio-politics. Second, the sublimation of colonialist ideology continues to be perpetuated by the church. Third, the normalization of religious hegemony results in the marginalization of local knowledge. The conclusion explains that Christianity has been sublimated to form a singular narrative, becoming a tool for elites to legitimize the socio-religious movements of the Minahasa community.